IMPLEMENTASI MODEL PEMBELAJARAN PBL DENGAN MEDIA VIDEO YOUTUBE PADA MATERI KELANGKAAN KEBUTUHAN MANUSIA UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN IPS SISWA KELAS VII MTS SABILUL MUTTAQIN TAHUN AJARAN 2024/2025 - Sharita Ramadhanti; Melinda Puspita; Dyah Novitasari; Dany Miftah M. Nur (Publikasi Inspirasi Indonesia, 2024)
This research aims to apply the Problem-Based Learning (PBL) learning model using YouTube video media on material about the scarcity of human needs in increasing students' interest in learning in social studies subjects in class VII MTs Sabilul Mutakin for the 2024/2025 academic year. The PBL approach was chosen because it is able to encourage students to be active, think critically, and solve problems independently or in groups. YouTube video media is used to support learning to make it more interactive and relevant to the needs of today's digital generation. This research uses a quasi-experimental method with a pretest-posttest control group design. The research subjects were class VII students at MTs Sabilul Mutakin who were divided into two groups: experimental class (using PBL with YouTube video media) and control class (using conventional methods). Data was collected through learning interest questionnaires, observations, and concept understanding tests. The research results show that the application of the PBL model with YouTube video media significantly increases students' interest in learning compared to conventional learning methods. Students are more motivated, actively involved in the learning process, and able to understand the concept of scarcity of human needs better. These findings indicate that the integration of the PBL model and digital media such as YouTube can be an effective learning innovation in improving the quality of social studies education.